INDUCED DEGRADATION OF CRUDE OIL POLLUTED SOIL BY MICROBIAL AUGMENTATION - SYLVESTER UWADIAE; EMIKE OMOAYENA (Journal of Engineering Studies and Research)
This study was aimed at assessing the effectiveness of indigenous microbes for remediation of hydrocarbon contaminated soil by first increasing the population of the indigenous microbes via bioaugmentation. Soil samples were treated using a consortium of bacteria: Bacillus substilis and Pseudomonas sp. which were isolated and cultured from the contaminated soil. The non-bacteria injected soil sample had the highest hydrocarbon content (THC) of 271.021 in comparison with the other soil samples. The THC percentage removal of B1 (96.885 %), B2 (97.562 %), B3 (98.835 %), B4 (99.594 %) and B5 (99.540 %) were higher than that of the control; indicating that biodegradation actually took place.